Feminist frontiers - Taylor, Verta A.; Rupp, Leila J. 1950-; Whittier, Nancy, 1966- (New York McGraw Hill Higher Education, 2009)
Introduction; Gender, culture, and socialization; Social organization of gender; Social change
Includes bibliographical references.
Keywords: Feminism -- United States; Women -- United States; Sex role -- United States; Women -- Cross-cultural studies; Nữ giới